2009
DOI: 10.1038/nrm2831
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and its toolbox for the maintenance of genome integrity

Abstract: The breast and ovarian cancer type 1 susceptibility protein (BRCA1) has pivotal roles in the maintenance of genome stability. Studies support that BRCA1 exerts its tumour suppression function primarily through its involvement in cell cycle checkpoint control and DNA damage repair. In addition, recent proteomic and genetic studies have revealed the presence of distinct BRCA1 complexes in vivo, each of which governs a specific cellular response to DNA damage. Thus, BRCA1 is emerging as the master regulator of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
468
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 449 publications
(489 citation statements)
references
References 122 publications
12
468
1
8
Order By: Relevance
“…BRCA1 tumor suppressor is known to have multiple functions, including its roles in DNA damage signaling, HR, and genome stability, and these functions have been implicated in tumor suppressor function (55). BRCA1 exists in multiple complexes, and these complexes are known to have independent as well as overlapping functions in genome maintenance (55).…”
Section: Discussionmentioning
confidence: 99%
“…BRCA1 tumor suppressor is known to have multiple functions, including its roles in DNA damage signaling, HR, and genome stability, and these functions have been implicated in tumor suppressor function (55). BRCA1 exists in multiple complexes, and these complexes are known to have independent as well as overlapping functions in genome maintenance (55).…”
Section: Discussionmentioning
confidence: 99%
“…PALB2 physically links BRCA1 and BRCA2 and plays an important role in HR repair (5). Interestingly, we found that BRCA1 promoted PALB2 phosphorylation at Ser-157, whereas phosphorylation of PALB2 Ser-376 was only marginally affected in the absence of BRCA1 (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Together with BRCA2, the PALB2-BRCA2 heterodimeric complex initiates high-fidelity homologous recombination (HR) 4 DNA repair by promoting the assimilation of the recombinase RAD51 onto resected 3Ј single-strand overhangs (1)(2)(3). Inactivation of PALB2 compromised RAD51 loading onto DNA breaks, greatly diminished HR repair, and hyper-sensitized cells to genotoxic stress (4,5). Consistent with the intimate links between dysregulated DNA repair and human tumorigenesis, PALB2 mutations predispose individuals to early onset of a number of cancers, including those of breast and pancreatic origins (6 -10).…”
mentioning
confidence: 99%
“…In humans, many factors involved in DDR and DNA repair, such as BRCA1 and BRCA2, are wellknown tumor suppressors. BRCA1 has been linked to both familial and sporadic breast and ovarian cancers, and it operates in multiple biological pathways including DDR and DNA repair (2,3). BRCA1 is essential for the homologous recombination (HR) repair pathway, and therefore, cells deficient in BRCA1 function are hypersensitive to ionizing radiation and other drugs that directly induce double-strand breaks (DSBs) (4).…”
mentioning
confidence: 99%